The Rice Basic Helix-Loop-Helix Transcription Factor TDR INTERACTING PROTEIN2 Is a Central Switch in Early Anther Development . Issue 4 (22nd April 2014) - Fu, Zhenzhen; Yu, Jing; Cheng, Xiaowei; Zong, Xu; Xu, Jie; Chen, Mingjiao; Li, Zongyun; Zhang, Dabing; Liang, Wanqi
Abstract : This report identifies the rice bHLH protein TIP2 as a key switch for the meristemoid transition and cell differentiation during early anther development. TIP2 directly triggers the expression of the developmental regulators TDR and EAT1 and interacts with TDR, forming a central cascade regulating differentiation, morphogenesis, and degradation of anther somatic cell layers. Abstract: In male reproductive development in plants, meristemoid precursor cells possessing transient, stem cell–like features undergo cell divisions and differentiation to produce the anther, the male reproductive organ. The anther contains centrally positioned microsporocytes surrounded by four distinct layers of wall: the epidermis, endothecium, middle layer, and tapetum. Here, we report that the rice ( Oryza sativa ) basic helix-loop-helix (bHLH ) protein TDR INTERACTING PROTEIN2 (TIP2) functions as a crucial switch in the meristemoid transition and differentiation during early anther development. The tip2 mutants display undifferentiated inner three anther wall layers and abort tapetal programmed cell death, causing complete male sterility. TIP2 has two paralogs in rice, TDR and EAT1, which are key regulators of tapetal programmed cell death. We revealed that TIP2 acts upstream of TDR and EAT1 and directly regulates the expression of TDR and EAT1 . In addition, TIP2 can interact with TDR, indicating a role of TIP2 in later anther development. Our findings suggest that the bHLH proteins TIP2, TDR, and EAT1 play a central role in regulating differentiation, morphogenesis, and degradation of anther somatic cell layers, highlighting the role of paralogous bHLH proteins in regulating distinct steps of plant cell–type determination.